2019
DOI: 10.18488/journal.73.2019.71.20.28
|View full text |Cite
|
Sign up to set email alerts
|

Principals Administrative Competence and Teachers Work Performance in Secondary Schools in Calabar Education Zone of Cross River State, Nigeria

Abstract: The focus of this study was to investigate "principals' administrative competence and teachers work performance" in Calabar Education zone. Four null hypotheses were tested in the course of the study. Correlational research design was adopted, while purposive sampling technique was used in selecting a sample of 800 teachers. Two instruments were used for data collection including "Principals' Administrative Competence Questionnaire (PACQ)," and Teachers' Work Performance Questionnaire (TWPQ)." Pearson Product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…For instance, Owan and Agunwa (2019) argued that the main effect of gender is not statistically significant on the performance of students in mathematics F (1, 249) = 0.353, p>.05, Partial η2 = .001, but the interactive effect of gender and birth order F(3,249)=2.854, p<.05, partial η2 =.034. The result emerging from the study of Adeleke (2007) showed that there is an insignificant statistical difference in the problem-solving performance of male and female students in simultaneous linear equations across three categories of students with (mean1 = 8.14; mean2 = 7.66, df = 122, t = .51, p< .05).…”
Section: Gender and Performance In Mathematicsmentioning
confidence: 99%
“…For instance, Owan and Agunwa (2019) argued that the main effect of gender is not statistically significant on the performance of students in mathematics F (1, 249) = 0.353, p>.05, Partial η2 = .001, but the interactive effect of gender and birth order F(3,249)=2.854, p<.05, partial η2 =.034. The result emerging from the study of Adeleke (2007) showed that there is an insignificant statistical difference in the problem-solving performance of male and female students in simultaneous linear equations across three categories of students with (mean1 = 8.14; mean2 = 7.66, df = 122, t = .51, p< .05).…”
Section: Gender and Performance In Mathematicsmentioning
confidence: 99%
“…Furthermore, authentic leadership has been described as having a positive effect on employee efficiency, worker satisfaction, confidence and cooperation with managers, corporate citizenship, organizational engagement, psychological energy, community loyalty, work environment, and financial success (Agwu & Agunwa, 2019;Erlangga, 2019;Gardner, Cogliser, Davis, & Dickens, 2011;Hadebe & Khumalo, 2018). Additionally, Duignan (2014); Kulophas and Hallinger (2019) conclude that in educational organizations substantial evidence confirms the arguments that credible education leaders use the combined constructive energy of core education partners to create a diverse, stimulating, and successful learning environment to deliver high-quality outcomes for students.…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…Principals' ability to communicate is a key factor in their effectiveness (Herrera, 2010). Effective principals are continuously searching for new strategies and means of communicating with their external and internal publics (Owan and Agunwa, 2019). Besides, principals need to realize that it would take more than verbal rhetoric to effectively communicate the goals and priorities of the school.…”
Section: Principals' Communication Patternsmentioning
confidence: 99%